Amphiphilic carbon dots, clean fracturing fluid and application of clean fracturing fluid
By preparing amphiphilic carbon dots and combining cationic surfactant and mineralized water, the ratio of clean fracturing fluid is optimized, and the problems of traditional fracturing fluids are solved, and the high-efficiency low-permeability oil reservoir is achieved. Development reduces production costs and water resources consumption.
Patent Information
- Application Number
- CN202411317816.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Traditional clean fracturing fluid has shortcomings in high temperature and salt resistance, which limits its application in the development of low permeability oil and gas reservoirs.
By preparing amphiphilic carbon dots, solvothermal reactions using organic acids and hydrophobic aliphatic compounds, nanoscale amphiphilic carbon dots are prepared and used as a key component of the cleaning fracturing fluid, combining cationic surfactants and Mineralized water, optimize the ratio to improve viscosity and high salt resistance.
It significantly improves the high temperature resistance and high salt resistance of clean fracturing fluid, reduces the usage and production costs, realizes the recycling of water resources, is suitable for hydraulic fracturing in low permeability and high mineralization reservoirs, and extends the Fracturing range.
Smart Images

Figure CN119286495A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydraulic fracturing, and in particular relates to an amphiphilic carbon dot, a clean fracturing fluid and applications thereof. Background Art
[0002] Low permeability oil and gas reservoirs in my country are an important unconventional oil and gas resource with abundant reserves but great difficulty in development. Hydraulic fracturing, as a key technology for the development of low permeability oil and gas reservoirs, is a measure to increase production and injection by using hydraulic force to form cracks in the formation and improve the flow of gas and oil. Fracturing fluid plays a vital role in the fracturing operation of oil and gas wells. Its main function is to increase the recoverable reserves of oil and gas by generating and maintaining cracks. Therefore, the performance of fracturing fluid has a decisive influence on the fracturing effect and the economic benefits of reservoir development. At present, guar polymer fracturing fluid is widely used due to its good sand carrying capacity and economic benefits. However, a large amount of guar residue will be produced after the fracturing operation, which will cause great damage to the formation. Conventional fracturing fluid has poor salt tolerance, and the preparation of the fluid requires a large amount of fresh water resources. The flowback and treatment process after fracturing is complicated. These problems limit its wider application.
[0003] In this context, viscoelastic surfactant (VES) fracturing fluid has developed rapidly in the field of oil and gas field development as a new type of fracturing fluid system. The viscosity of VES fracturing fluid is mainly caused by the worm-like micelles formed by the surfactant in the aqueous solution. Compared with traditional guar polymer fracturing fluid, VES fracturing fluid has significant advantages in sand carrying capacity, fracturing effect and environmental friendliness. When encountering hydrocarbon substances, it can completely break the gel without residue and cause less damage to the formation. The main component of VES fracturing fluid is a small molecule surfactant, so it is easy to flow back after breaking the gel, so it is called "clean fracturing fluid". However, VES fracturing fluid still faces certain challenges in terms of high temperature resistance and cost.
[0004] Therefore, how to prepare clean fracturing fluid that is resistant to high temperature and salt has become an urgent problem to be solved. Summary of the invention
[0005] In view of the above-mentioned deficiencies, the object of the present invention is to provide an amphiphilic carbon dot, a clean fracturing fluid and applications thereof, so as to solve the technical problems of poor high temperature resistance and salt resistance of conventional clean fracturing fluids.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides an amphiphilic carbon dot, which is prepared by a solvothermal reaction of an organic acid and a hydrophobic aliphatic compound.
[0007] Preferably, the organic acid includes one or more of citric acid, tartaric acid, malic acid, salicylic acid, and hydroxybenzoic acid; the hydrophobic aliphatic compound includes one or more of fatty acids, fatty alcohols, and alkylamines.
[0008] Preferably, the fatty acid includes one or more of saturated fatty acids, unsaturated fatty acids, and aromatic fatty acids; the fatty alcohol includes one or more of n-octanol, n-dodecanol, n-tetradecanol, and n-hexadecanol; and the alkylamine includes one or more of n-octylamine, dodecylamine, and tetradecanol.
[0009] Preferably, the mass ratio of the organic acid to the hydrophobic aliphatic compound is (1:1) to (1:5).
[0010] Preferably, the solvent used in the solvothermal reaction includes one or more of water, ethanol, DMF, DMSO, CCl4, and PEG.
[0011] Preferably, the reaction temperature of the solvothermal reaction is 140-190° C., and the reaction time is 8-16 h.
[0012] In a second aspect, the present invention provides a clean fracturing fluid, comprising a cationic surfactant, mineralized water, and the amphiphilic carbon dots as described in the first aspect; wherein the mineralization degree of the mineralized water is 50,000~250,000 mg / L.
[0013] Preferably, the total mass of the cationic surfactant and the amphiphilic carbon dots is 1.0% to 4.0% of the total mass of the clean fracturing fluid; and the mass ratio of the cationic surfactant to the amphiphilic carbon dots is (6 to 9): (1 to 4).
[0014] Preferably, the cationic surfactant is one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide; and the salt in the mineralized water includes an inorganic salt.
[0015] In a third aspect, the present invention provides a use of the clean fracturing fluid as described in the second aspect in hydraulic fracturing of low permeability reservoirs and / or high salinity reservoirs.
[0016] The beneficial effects of the present invention are: The amphiphilic carbon dots provided by the present invention are obtained from an organic acid and a hydrophobic aliphatic compound by a one-step solvothermal method. By changing the type of the hydrophobic aliphatic compound, hydrophobic groups with different properties and different carbon chain lengths can be introduced, thereby achieving the simple preparation of amphiphilic carbon dots with different structures and properties.
[0017] The amphiphilic carbon dots proposed in the present invention are nanometer-sized and are used as a key component of clean fracturing fluid. Their nanometer-sized effect can effectively penetrate into the dense pore throats and microcracks of low-permeability reservoirs, reduce fluid flow resistance, and extend the range of fracturing action, thereby greatly improving the effect of fracturing operations.
[0018] The amphiphilic carbon dots proposed in the present invention can significantly increase the viscosity of cationic surfactants in high-mineralization water. By screening the optimal ratio of the two, the amount of clean fracturing fluid can be greatly reduced, thereby reducing production costs.
[0019] The clean fracturing fluid prepared by the present invention using amphiphilic carbon dots is not only resistant to high temperatures and suitable for reservoirs with higher temperatures, but also resistant to high salts, avoiding dependence on fresh water. It can be prepared using seawater or fracturing flowback fluid, thus achieving the recycling of water resources, meeting the requirements of green environmental protection and sustainable development, and providing an environmentally friendly and efficient solution for the application of clean fracturing fluid. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0021] Figure 1 This is the effect curve of the mass ratio of CTAB to CDs-2 on the viscosity of clean fracturing fluid; Figure 2 This is the effect curve of the total amount of CTAB and CDs-2 on the viscosity of the clean fracturing fluid; Figure 3 This is the effect curve of the mineralized water ion type and concentration on the viscosity of the clean fracturing fluid; Figure 4 18 and 19 are the viscosity-temperature curves of the clean fracturing fluids. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] As a new type of nanomaterial, carbon dots have good adaptability to low permeability reservoirs, mainly manifested in: 1) The nano-size effect of carbon dots enables them to effectively penetrate into the pore throat structure of low-permeability reservoirs. They can be used as additives in fracturing fluids to improve the ability of fracture expansion, especially in microcracks and capillary pores, thereby improving reservoir permeability. At the same time, their high penetration ability can effectively reduce the amount of carbon dots used and reduce the overall cost of fracturing fluids. 2) The high surface activity of carbon dots can significantly reduce the interfacial tension between fracturing fluid and crude oil, change the wettability of rocks, help fracturing fluids to effectively penetrate into the reservoir environment, and extend the fracturing distance. Their excellent surface activity helps with the flowback of fracturing fluids after operation. 3) Carbon dots can be used as tracers due to their fluorescent properties to monitor the flow path and distribution of fracturing fluids in reservoirs, which helps to evaluate the fracturing effect and adjust the fracturing plan in a timely manner. 4) Carbon dots have a wide range of raw materials, and the preparation method is simple and diverse, with good cost-effectiveness. 5) Carbon dots have good biocompatibility and environmental degradability, so they have little environmental impact during the fracturing process. The inventors of the present invention realize that amphiphilic carbon dots have hydrophilic and lipophilic properties. If used as nano-sized surfactants, they will have good adaptability to low permeability reservoirs. Therefore, using amphiphilic carbon dots to replace the traditional VES system is expected to reduce the cost of clean fracturing fluid and improve the fracturing effect, which has good application prospects for promoting the efficient development of low permeability reservoirs.
[0024] In view of this, in a first aspect, an embodiment of the present application provides an amphiphilic carbon dot, which is prepared by a solvothermal reaction of an organic acid and a hydrophobic aliphatic compound.
[0025] In some preferred embodiments, the organic acid includes one or more of citric acid, tartaric acid, malic acid, salicylic acid, and hydroxybenzoic acid; the hydrophobic aliphatic compound includes one or more of fatty acids, fatty alcohols, and alkylamines. Among them, fatty acids include but are not limited to one or more of saturated fatty acids, unsaturated fatty acids, and aromatic fatty acids; for example, saturated fatty acids may be one or more of lauric acid, palmitic acid, and stearic acid, unsaturated fatty acids may be one or more of oleic acid, linoleic acid, and ricinoleic acid, and aromatic fatty acids may be one or more of benzoic acid and p-methylbenzoic acid. Fatty alcohols include but are not limited to one or more of n-octanol, n-dodecyl alcohol, n-tetradecanol, and n-hexadecanol; alkylamines include but are not limited to one or more of n-octylamine, dodecylamine, and tetradecanol.
[0026] In some preferred embodiments, a method for preparing amphiphilic carbon dots comprises the following steps: The organic acid, the hydrophobic aliphatic compound and the solvent are mixed, and then the solvent thermal reaction is carried out at 140-190°C for 8-16 hours, and the amphiphilic carbon dots are obtained by post-treatment. The mass ratio of the organic acid to the hydrophobic aliphatic compound is (1:1)-(1:5). The solvent includes but is not limited to one or more of water, ethanol, DMF, DMSO, CCl4, and PEG; the mass ratio of the organic acid to the solvent is (1:10)-(1:100).
[0027] In some preferred embodiments, the post-processing steps after the reaction are completed can be: after the reaction is completed, the reaction mixture is cooled, and then centrifugally filtered and the solvent is dried to obtain a crude product; the crude product is dissolved in water and dialyzed (dialysis bag of 500-2000 Da), and freeze-dried to obtain amphiphilic carbon dots.
[0028] In a second aspect, an embodiment of the present application provides a clean fracturing fluid, comprising a cationic surfactant, mineralized water, and the amphiphilic carbon dots as described in the first aspect; wherein the mineralization degree of the mineralized water is 50,000~250,000 mg / L; the total mass of the cationic surfactant and the amphiphilic carbon dots is 1.0%~4.0% of the total mass of the clean fracturing fluid; and the mass ratio of the cationic surfactant to the amphiphilic carbon dots is (6~9):(1~4).
[0029] In some preferred embodiments, the cationic surfactant is one or more of dodecyl trimethyl ammonium bromide, tetradecyl trimethyl ammonium bromide, hexadecyl trimethyl ammonium bromide, and octadecyl trimethyl ammonium bromide. Mineralized water is prepared by dissolving an inorganic salt in water, and the inorganic salt includes but is not limited to one or more of sodium chloride, calcium chloride, and potassium chloride.
[0030] In a third aspect, an embodiment of the present application provides a use of the clean fracturing fluid as described in the second aspect in hydraulic fracturing of low permeability reservoirs and / or high salinity reservoirs.
[0031] In order to make the implementation objectives, technical solutions and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be described in more detail below in conjunction with the accompanying drawings of the present invention.
[0032] Example 1 A preparation method of an amphiphilic carbon dot is as follows: 1.0 g of salicylic acid and 1.5 g of dodecanol are weighed and placed in a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, 40 mL of anhydrous ethanol is added, dissolved and mixed evenly. The sealed autoclave is placed in an oil bath and heated at 160° C. for 8 h. When the autoclave is cooled to room temperature, the reaction solution is taken out and placed in a centrifuge tube, and the insoluble matter is removed by centrifugal filtration at a rate of 5000 rpm, and then the solvent is concentrated and evaporated by rotary evaporation to obtain a crude product, which is redispersed in water, and dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 500 Da, and then freeze-dried after dialysis to obtain an amphiphilic carbon dot, which is recorded as CDs-1.
[0033] Example 2 A preparation method of an amphiphilic carbon dot is as follows: 1.0g of citric acid, 1.5g of n-octylamine and 1.0g of tetradecanol are weighed and placed in a 50mL stainless steel autoclave lined with polytetrafluoroethylene, 10mL of deionized water and 30mL of ethanol are added, dissolved and mixed evenly. The sealed autoclave is placed in an oil bath and heated at 180°C for 12h. When the autoclave is cooled to room temperature, the reaction solution is taken out in a centrifuge tube, and the insoluble matter is removed by centrifugal filtration at a rate of 5000rpm, and then the solvent is concentrated and evaporated by rotary evaporation to obtain a crude product, which is redispersed in water, and dialyzed for 48h using a dialysis bag with a molecular weight cutoff of 500Da, and then freeze-dried after dialysis to obtain an amphiphilic carbon dot, which is recorded as CDs-2.
[0034] Example 3 A preparation method of an amphiphilic carbon dot is as follows: 1.5 g malic acid, 3.5 g dodecylamine and 0.2 g stearic acid are weighed and placed in a 50 mL polytetrafluoroethylene-lined stainless steel autoclave, 20 mL DMF and 20 mL CCl4 are added, dissolved and mixed evenly. The sealed autoclave is placed in an oil bath and heated at 180° C. for 14 h. When the autoclave is cooled to room temperature, the reaction solution is taken out into a centrifuge tube, and the insoluble matter is removed by centrifugal filtration at a rate of 5000 rpm, and then the solvent is concentrated and evaporated by rotary evaporation to obtain a crude product, which is redispersed in water, and dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 500 Da, and then freeze-dried after dialysis to obtain an amphiphilic carbon dot, which is recorded as CDs-3.
[0035] Example 4 A clean fracturing fluid is prepared by: weighing 200g NaCl in a beaker, adding 500mL distilled water to dissolve, and diluting the solution into a 1000mL volumetric flask to obtain a mineralized aqueous solution; weighing 1.2g of the amphiphilic carbon dot CDs-1 prepared in Example 1 and 3.6g of dodecyltrimethylammonium bromide in a 250mL beaker, and then adding 150mL of mineralized water, stirring for 60min under mechanical stirring at 700rpm to obtain a clean fracturing fluid.
[0036] Example 5 A clean fracturing fluid is prepared by: weighing 200 g NaCl and 10 g CaCl2 in a beaker, adding 500 mL distilled water to dissolve, and diluting the solution into a 1000 mL volumetric flask to obtain a mineralized aqueous solution; weighing 0.6 g CDs-2 prepared in Example 2 and 2.4 g CTAB in a 250 mL beaker, adding 150 mL of mineralized water, and stirring for 60 min under mechanical stirring at 700 rpm to obtain a clean fracturing fluid.
[0037] Example 6 A clean fracturing fluid is prepared by: weighing 200g NaCl and 10g CaCl2 in a beaker, adding 500mL distilled water to dissolve, and diluting the volume into a 1000mL volumetric flask to obtain a mineralized aqueous solution; weighing 0.6g CDs-3 prepared in Example 3 and 2.4g CTAB in a 250mL beaker, and then adding 150mL of mineralized water, stirring for 60min under mechanical stirring at 700rpm to obtain a clean fracturing fluid.
[0038] Example 7 A clean fracturing fluid is prepared by: weighing 200g NaCl and 10g CaCl2 in a beaker, adding 500mL distilled water to dissolve, and diluting the volume into a 1000mL volumetric flask to obtain a mineralized aqueous solution; weighing 2.0g of the amphiphilic carbon dots CDs-3 prepared in Example 3 and 2.0g CTAB in a 250mL beaker, and then adding 150mL of mineralized water, stirring for 60min under mechanical stirring at 700rpm to obtain a clean fracturing fluid.
[0039] Example 8 A clean fracturing fluid is prepared in the same manner as in Example 5, except that 0.3 g of CDs-2 and 2.7 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 9:1.
[0040] Example 9 A clean fracturing fluid is prepared in the same manner as in Example 5, except that 0.9 g of CDs-2 and 2.1 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 7:3.
[0041] Example 10 A clean fracturing fluid is prepared in the same manner as in Example 5, except that 1.2 g of CDs-2 and 1.8 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 6:4.
[0042] Embodiment 11 A clean fracturing fluid is prepared in the same manner as in Example 5, except that the total mass of CTAB and CDs-2 is 1.0% of the total mass of the fracturing fluid.
[0043] Example 12 A clean fracturing fluid is prepared in a method substantially the same as that of Example 5, except that the total mass of CTAB and CDs-2 is 1.5% of the total mass of the fracturing fluid.
[0044] Embodiment 13 A clean fracturing fluid is prepared in the same manner as in Example 5, except that the total mass of CTAB and CDs-2 is 3.0% of the total mass of the fracturing fluid.
[0045] Embodiment 14 A clean fracturing fluid is prepared in substantially the same manner as in Example 5, except that the total mass of CTAB and CDs-2 is 4.0% of the total mass of the fracturing fluid.
[0046] Embodiment 15 A clean fracturing fluid, the preparation method is basically the same as that of Example 5, except that the mineralized water is 5×10 4 mg / L, 10×10 4 mg / L, 15×10 4 mg / L, 20×10 4 mg / L NaCl solution.
[0047] Example 16 A clean fracturing fluid, the preparation method is basically the same as that of Example 5, except that the mineralized water is 5×10 4 mg / L, 10×10 4 mg / L, 15×10 4 mg / L, 20×10 4 mg / L KCl solution.
[0048] Embodiment 17 A clean fracturing fluid, the preparation method is basically the same as that of Example 5, except that the mineralized water is 5×10 4 mg / L, 10×10 4 mg / L, 15×10 4 mg / L, 20×10 4 mg / L CaCl2 solution.
[0049] Embodiment 18 A clean fracturing fluid is prepared in substantially the same manner as in Example 5, except that the mineralized water is a 200,000 mg / L NaCl solution.
[0050] Embodiment 19 A clean fracturing fluid is prepared in substantially the same manner as in Example 5, except that the mineralized water is 200,000 mg / L NaCl, and the total mass of CTAB and CDs-2 is 4.0% of the total mass of the fracturing fluid.
[0051] Comparative Example 1 The preparation method is basically the same as that of Example 5, except that 0.6 g of CDs-2 is replaced by CTAB to obtain a clean fracturing fluid without amphiphilic carbon dots.
[0052] Comparative Example 2 A clean fracturing fluid is prepared in the same manner as in Example 5, except that 1.5 g of CDs-2 and 1.5 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 5:5.
[0053] Comparative Example 3 A clean fracturing fluid is prepared in the same manner as in Example 5, except that 2.1 g of CDs-2 and 0.9 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 3:7.
[0054] Comparative Example 4 A clean fracturing fluid is prepared by a method substantially the same as that of Example 5, except that 2.7 g of CDs-2 and 0.3 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 1:9.
[0055] Comparative Example 5 A clean fracturing fluid is prepared in the same manner as in Example 5, except that 3.0 g of CDs-2 and 0 g of CTAB are used, that is, the mass ratio of CTAB to CDs-2 is 0:10.
[0056] Comparative Example 6 The preparation method is basically the same as that of Example 5, except that the mineralized water is replaced with tap water to obtain a clean fracturing fluid that does not contain high-mineralization salt ions.
[0057] Comparative Example 7 The preparation method is basically the same as that of Example 5, except that the mineralized water is replaced with distilled water to obtain a clean fracturing fluid free of metal salt ions.
[0058] Performance Testing The clean fracturing fluids prepared in each embodiment and comparative example were measured using an eight-speed rotational viscometer. The test conditions were: 25°C, 170s -1 .
[0059] Figure 1 The curves of the influence of the mass ratio of CTAB to CDs-2 on viscosity for Example 5, Examples 8 to 10 and Comparative Examples 1 to 5 are shown. The total dosage of the two is 2%, and the mineralized water components include 200,000 mg / L NaCl and 10,000 mg / L CaCl2. It can be seen that when the ratio of CTAB to CDs-2 is adjusted from 10:0 to 6:4, as the content of CDs-2 increases, the viscosity of the fracturing fluid first increases and then decreases, but the viscosity of the compound system is greater than that of pure CTAB, indicating that CDs has a viscosity-increasing effect on CTAB; when the proportion of CDs-2 exceeds 50%, it will have an adverse effect on the viscosity, so the optimal ratio of the two is 8:2, and the effect of Example 5 is the best.
[0060] Figure 2 The effect curve of the total amount of CTAB and CDs-2 mixture on viscosity in Examples 5 and 11-14. Among them, CTAB:CDs-2=8:2 (mass ratio), and the mineralized water components include 200,000 mg / L NaCl and 10,000 mg / L CaCl2. As can be seen from the figure, with the increase of the total amount, the viscosity of the clean fracturing fluid is significantly improved, and a 4% amount can reach 300mPa·s. Compared with the 6% amount required for traditional clean fracturing fluid, the amount is reduced to a certain extent, reducing the production cost.
[0061] Figure 3 The curves of the influence of the ion types and concentrations of mineralized water on the viscosity of clean fracturing fluid in Examples 15 to 17 are shown. CTAB:CDs-2=8:2 (mass ratio), and the total dosage is 2%. The results show that when the mineralization is lower than 50,000 mg / L, the viscosity-increasing effect is not significant. As the mineralization increases, the viscosity increases accordingly. In contrast, the mineralized water reaches the best under 200,000 mg / L NaCl solution.
[0062] Figure 4 The viscosity-temperature curves of the clean fracturing fluids in Examples 18 and 19. CTAB:CDs-2=8:2 (mass ratio), and the mineralized water component is 200,000 mg / L NaCl. The results show that the viscosity of the fracturing fluid increases first and then decreases with increasing temperature, reaching the maximum viscosity at 40°C. The industry standard SY / T 6376-2008 "General Technical Conditions for Fracturing Fluids" on "General Technical Indicators for Viscoelastic Surfactant Fracturing Fluids" requires that the apparent viscosity of the "heat and shear resistance" of such fracturing fluids be ≥20mPa·s. It can be seen that the maximum tolerable temperature of the fracturing fluid of the present invention is 75°C at a dosage of 2%, and can reach 92°C at a dosage of 4%, solving the problem of the traditional clean fracturing fluid being not resistant to high temperatures.
[0063] Compared with Example 5, the viscosity of Comparative Examples 6 and 7 is 0, indicating that the metal salt ions in the clean fracturing fluid system play an important role in its viscosity. It also shows that the fracturing fluid provided by the present invention has good salt resistance and can be used for the development of low-permeability and high-mineralization oil reservoirs.
[0064] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0065] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An amphiphilic carbon dot, characterized in that: The amphiphilic carbon dots are prepared by solvent thermal reaction of an organic acid and a hydrophobic aliphatic compound.
2. The amphiphilic carbon dots according to claim 1, characterized in that The organic acid includes one or more of citric acid, tartaric acid, malic acid, salicylic acid, and hydroxybenzoic acid; the hydrophobic aliphatic compound includes one or more of fatty acids, fatty alcohols, and alkylamines.
3. The amphiphilic carbon dots according to claim 2, characterized in that The fatty acid includes one or more of saturated fatty acids, unsaturated fatty acids, and aromatic fatty acids; the fatty alcohol includes one or more of n-octanol, n-dodecyl alcohol, n-tetradecyl alcohol, and n-hexadecanol; and the alkylamine includes one or more of n-octylamine, dodecylamine, and tetradecylamine.
4. The amphiphilic carbon dots according to claim 1, characterized in that The mass ratio of the organic acid to the hydrophobic aliphatic compound is (1:1) to (1:5).
5. The amphiphilic carbon dots according to claim 1, characterized in that The solvent used in the solvothermal reaction includes one or more of water, ethanol, DMF, DMSO, CCl4, and PEG.
6. The amphiphilic carbon dots according to claim 1, characterized in that The reaction temperature of the solvent thermal reaction is 140-190° C., and the reaction time is 8-16 h.
7. A clean fracturing fluid, characterized in that: It comprises a cationic surfactant, mineralized water, and the amphiphilic carbon dots according to any one of claims 1 to 6; wherein the mineralization degree of the mineralized water is 50,000 to 250,000 mg / L.
8. The clean fracturing fluid according to claim 7, characterized in that: The total mass of the cationic surfactant and the amphiphilic carbon dots is 1.0% to 4.0% of the total mass of the clean fracturing fluid; the mass ratio of the cationic surfactant to the amphiphilic carbon dots is (6 to 9): (1 to 4).
9. The clean fracturing fluid according to claim 7, characterized in that: The cationic surfactant is one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide; and the mineralized water contains inorganic salts.
10. Use of the clean fracturing fluid according to any one of claims 7 to 9 in hydraulic fracturing of low permeability reservoirs and / or high salinity reservoirs.
Citation Information
Patent Citations
Preparation method and application of amphiphilic carbon quantum dots
CN116654911A
Amphiphilic nano oil displacement agent for high-temperature and high-salinity oil reservoir and application of amphiphilic nano oil displacement agent
CN117070203A
KR20240127300A
Cited By
Nano demulsifier as well as preparation method and application thereof
CN120248364A
Amphiphilic carbon dots, carbon nanofluid and application of amphiphilic carbon dots and carbon nanofluid
CN120504314A
Amphiphilic carbon dots, rapid-dispersion super-stable foam system and preparation method of rapid-dispersion super-stable foam system
CN122126834A
An amphiphilic carbon dot, a rapid dispersion ultra-stable foam system and a preparation method thereof
CN122126834B